Enhancement of the Electrocatalytic Activity of Thienyl-Substituted Iron Porphyrin Electropolymers by a Hangman Effect - Neumann, Bettina; Goetz, Robert; Wrzolek, Pierre; Scheller, Frieder W.; Weidinger, Inez M.; Schwalbe, Matthias; Wollenberger, Ulla (ChemCatChem, 2018)
The thiophene-modified iron porphyrin FeT3ThP and the respective iron Hangman porphyrin FeH3ThP, incorporating a carboxylic acid hanging group in the second coordination sphere of the iron center, were electropolymerized on glassy carbon electrodes using 3,4-ethylenedioxythiophene (EDOT) as co-monomer. Scanning electron microscopy images and Resonance Raman spectra demonstrated incorporation of the porphyrin monomers into a fibrous polymer network. Porphyrin/polyEDOT films catalyzed the reduction of molecular oxygen in a four-electron reaction to water with onset potentials as high as +0.14 V vs. Ag/AgCl in an aqueous solution of pH 7. Further, FeT3ThP/polyEDOT films showed electrocatalytic activity towards reduction of hydrogen peroxide at highly positive potentials, which was significantly enhanced by introduction of the carboxylic acid hanging group in FeH3ThP. The second coordination sphere residue promotes formation of a highly oxidizing reaction intermediate, presumably via advantageous proton supply, as observed for peroxidases and catalases making FeH3ThP/polyEDOT films efficient mimics of heme enzymes.
CRIS-Team Scopus Importer:2022-04-14
Keywords: activation of oxygen species; electro-polymerization; Hangman porphyrin; heterogeneous catalysis; immobilization